2013
DOI: 10.1093/bioinformatics/btt287
|View full text |Cite
|
Sign up to set email alerts
|

REDItools: high-throughput RNA editing detection made easy

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
227
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 264 publications
(237 citation statements)
references
References 14 publications
2
227
0
Order By: Relevance
“…In all cases, the consensus sequence deriving from deep sequencing coincided with the one determined by Sanger sequencing, confirming the cosegregation of newly identified variants with the known EBNA2 alleles. We also found one or more variable positions in all HDs (1-17) and individuals with MS (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). For all couples of variants lying on the same read (coverage $50), the hypothesis of independent segregation, indicative of random sequencing errors, was rejected through a x 2 test (p , 0.05), thus supporting the coexistence of different genotypes.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In all cases, the consensus sequence deriving from deep sequencing coincided with the one determined by Sanger sequencing, confirming the cosegregation of newly identified variants with the known EBNA2 alleles. We also found one or more variable positions in all HDs (1-17) and individuals with MS (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). For all couples of variants lying on the same read (coverage $50), the hypothesis of independent segregation, indicative of random sequencing errors, was rejected through a x 2 test (p , 0.05), thus supporting the coexistence of different genotypes.…”
Section: Resultsmentioning
confidence: 67%
“…18 The viral allele assignment of both amplicon and Sanger EBNA2 sequences was performed using a methodology implemented in a python script (available on request). Further details on the EBNA2 amplicon deep sequencing and analysis can be found in appendix e-1 on the Neurology ® Web site at Neurology.org.…”
mentioning
confidence: 99%
“…Next, we excluded cells with fewer than 1 million uniquely aligned reads and a mapping rate <70%, reducing the starting data set to 268 cells. On average, we analyzed 2.3 million reads per cell (Supplemental Table 1), calling RNA editing events using REDItools (Picardi and Pesole 2013) and retaining only sites supported by at least 10 independent reads.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, improved methods to robustly characterize genome-wide RE events (Danecek et al 2012;Ramaswami et al 2012;Picardi and Pesole 2013) have enabled genome-wide characterization of RE in several, mostly nondiseased, tissues (Danecek et al 2012;Park et al 2012;Lagarrigue et al 2013;Bazak et al 2014;Blanc et al 2014;Han et al 2015). To date, however, only a few studies have reported RE events at a genome-wide scale in disease tissues; for example, Han et al (2015) showed that in various cancer types RE events are associated with survival and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…After removal of known single nucleotide variants (SNVs) and using stringent filters for base (quality score > 25) and mapping quality (quality score > 20) (see Methods), we identified 201,322 unique mRNA sites with an alternate allele significantly different from its corresponding DNA sequence in at least one sample (BH-corrected P-value < 0.05, using REDItools) (Supplemental Fig. S1; Picardi and Pesole 2013). This set of candidate RE sites was further analyzed to minimize other potential sources of systematic bias, including variant distance bias (VDB; i.e., to account for false variants that tend to occur at a fixed distance from the end of reads), removal of read sequences with very high similarity (>95%) with other genomic regions, and strand bias (i.e., to account for variants observed only in either the forward or reverse strand of mapped reads) (see Figure 1. (A) Summary of study design for detecting significant differential RNA editing events associated with epilepsy.…”
Section: Methodsmentioning
confidence: 99%